2020
DOI: 10.1016/j.psj.2020.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of dietary calcium and phytase on broilers challenged with subclinical necrotic enteritis: part 2. Gut permeability, phytate ester concentrations, jejunal gene expression, and intestinal morphology

Abstract: Calcium has the capacity to interact with phytate-P to form Ca-phytate complexes and decrease the ability of exogenous phytase to degrade phytic acid. This study investigated the hypothesis that high dietary Ca would impair gut permeability, phytate esters (inositol x-phosphate, IPx: IP3, IP4, IP5, and IP6) degradation, jejunal gene expression, and intestinal morphology. Ross 308 day-old male broilers (n = 768) were distributed into 48-floor pens each housing 16 birds in a factorial arrangement. Factors were N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 71 publications
(88 reference statements)
0
10
0
Order By: Relevance
“… Proszkowiec-Weglarz et al (2019) reported that CASR plays a key role in regulating calcium homeostasis of chickens and exists in Ca 2+ regulatory tissues such as parathyroid, kidney, and intestine. Through CASR, parathyroid chief cells can maintain Ca 2+ concentrations in plasma by modulating release of parathyroid hormone into the circulation, and its levels are influenced by plasma vitamin D 3 and Ca ( Zanu et al, 2020 ). The characterization of CASR in intestinal epithelial cells indicates that CASR may mediate Ca 2+ absorption ( Gama, et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“… Proszkowiec-Weglarz et al (2019) reported that CASR plays a key role in regulating calcium homeostasis of chickens and exists in Ca 2+ regulatory tissues such as parathyroid, kidney, and intestine. Through CASR, parathyroid chief cells can maintain Ca 2+ concentrations in plasma by modulating release of parathyroid hormone into the circulation, and its levels are influenced by plasma vitamin D 3 and Ca ( Zanu et al, 2020 ). The characterization of CASR in intestinal epithelial cells indicates that CASR may mediate Ca 2+ absorption ( Gama, et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this hypothesis, Su et al 12 reported that SLC15A1 mRNA levels were decreased in the jejunum and increased in the ileum of Eimeria acervulina -challenged layers. C.perfringens -challenged chickens showed a down-regulation of SLC34A2 gene, which is involved in regulating both intestinal Pi (phosphate) absorption and renal Pi resorption, and of VDR gene, a transcription factor that mediates the vitamin D3, involved in signalling intestinal calcium and phosphate absorption 16 . This reduction of SLC34A2 may be explained by the decrease of mTOR , known to stimulate many intestinal NTers including SLC34A2 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Five villi per section were randomly selected for measurements of villus height, crypt depth, basal width, middle width, and apical width, resulting in 10 measurements per sample and 30 measurements per pen. The apparent villus surface area was calculated as (basal width + apical width)/2 × villus height, following Zanu et al (2020b).…”
Section: Morphometric Measurements Of Jejunummentioning
confidence: 99%